Systematic review of bidirectional interaction between gut microbiome, miRNAs, and human pathologies - Drago, Lorenzo; De La Motte, Luigi Regenburgh; Deflorio, Loredana; Sansico, Delia Francesca; Salvatici, Michela; Micaglio, Emanuele; Biazzo, Manuele; Giarritiello, Fabiana (Frontiers in Microbiology, 2025)
MicroRNAs (miRNAs) and the gut microbiome are key regulators of human health, with emerging evidence highlighting their complex, bidirectional interactions in chronic diseases. miRNAs, influence gene expression and can modulate the composition and function of the gut microbiome, impacting metabolic and immune processes. Conversely, the microbiome can affect host miRNA expression, influencing inflammatory pathways and disease susceptibility. This systematic review examines recent studies (2020–2024) focusing exclusively on human subjects, selected through rigorous inclusion and exclusion criteria. Studies were included if they investigated the interaction between miRNAs and the gut microbiome in the context of gastrointestinal diseases, obesity, autoimmune diseases, cognitive and neurodegenerative disorders, and autism. In vitro, in vivo and in silico analyses were excluded to ensure a strong translational focus on human pathophysiology. Notably, miRNAs, stable and abundant in patients, are emerging as promising biomarkers of microbiome-driven inflammation. This systematic review provides an overview of miRNAs, their regulatory effects on bacterial strains, and their associations with specific diseases. It also explores therapeutic advances and the potential of miRNA-based therapies to restore microbial balance and reduce inflammation.